2000
DOI: 10.1097/00043426-200011000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestation of β-Thalassemia/Hemoglobin E Disease

Abstract: These clinical features observed in patients with beta-thalassemia/Hb E are probably the results of chronic anemia and iron overload. The study of the life history and clinical courses of patients with beta-thalassemia/Hb E should provide important information for the better management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 14 publications
1
74
0
Order By: Relevance
“…Five (6.94 %) patients in the study group developed PTHN after splenectomy. Fucharoen et al [7] reported cardiovascular complications, including congestive heart failure in 11.9 % of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five (6.94 %) patients in the study group developed PTHN after splenectomy. Fucharoen et al [7] reported cardiovascular complications, including congestive heart failure in 11.9 % of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Splenomegaly often develops in severely affected patients. In the past, splenectomy was routinely performed in an attempt to increase hemoglobin levels [7]. The present study conducted to assess how post-splenectomy Hb E-b thalassaemia patients progress both in terms of clinical profile as well as laboratory investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCD patients are not the only patients with congenital hemolytic anemia to develop skin ulcerations, and they have been reported in thalassemia intermedia [18], hereditary spherocytosis [19], pyruvate kinase deficiency [20], and congenital dyserythropoietic anemia [21]. Ulcer prevalence in other types of congenital hemolytic anemias is not known, but their occurrence suggests that sickling is not a conditio sine qua non for ulcer formation, while chronic anemia and hemolysis appear to be common factors.…”
Section: Epidemiologymentioning
confidence: 99%
“…The clinical and hematological parameters in patients with HbE/ β-thalassemia vary from patient to patient [3][4][5][6][7]. The phenotypic variability of this co-inheritance and the lack of understanding of the possible mechanisms have imposed greater challenges in the management of Hb E/β-thalassemia affected individuals [8].…”
Section: Introductionmentioning
confidence: 99%